2017
DOI: 10.1016/j.hpb.2017.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization in hepatocellular carcinoma with portal vein tumor thrombosis: a systematic review and meta-analysis

Abstract: TACE is a safe treatment for a highly selected population of HCC patients with PVT. Despite worse survival rates compared to PVB thrombosis, PVT in the MPV should not be considered an absolute contraindication to TACE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 29 publications
2
85
0
3
Order By: Relevance
“…313 Impaired portal vein blood flow (for example, a portal vein thrombus, hepatofugal blood flow) is considered an absolute contraindication for TACE, although it can be performed safely in patients with segmental or sub-segmental portal vein obstruction if the treatment is selective. 525 However, TACE is not recommended in patients with segmental portal vein tumour invasion. Such indications should be discussed in multidisciplinary team sessions, in light of TARE and alternative first and second-line systemic treatments.…”
Section: Patient Selectionmentioning
confidence: 99%
“…313 Impaired portal vein blood flow (for example, a portal vein thrombus, hepatofugal blood flow) is considered an absolute contraindication for TACE, although it can be performed safely in patients with segmental or sub-segmental portal vein obstruction if the treatment is selective. 525 However, TACE is not recommended in patients with segmental portal vein tumour invasion. Such indications should be discussed in multidisciplinary team sessions, in light of TARE and alternative first and second-line systemic treatments.…”
Section: Patient Selectionmentioning
confidence: 99%
“…In a meta-analysis of PVTT patients treated with TACE, 1% experienced liver failure and 18% had posttreatment complications. 44 Due to the potential risk of hepatic failure following ischemic liver injury, TACE is traditionally contraindicated in patients with PVTT involving the main portal trunk or the first-order branches. 45 In recent years, an increasing number of studies have explored the role of TACE in the management of patients with PVTT.…”
Section: Transarterial Chemoembolizationmentioning
confidence: 99%
“…Meta-analysis among PVTT patients receiving TACE showed that TACE was associated with a survival benefit for patients with branch portal vein involvement compared with those with main portal vein involvement. 44 Although there are multiple staging systems for PVTT, these were largely developed for hepatic resection evaluation. Assessment of liver function with Child-Pugh classification appears to prognosticate for patients with unresectable HCC treated with TACE.…”
Section: Transarterial Chemoembolizationmentioning
confidence: 99%
“…75 A systematic review and meta-analysis examined the efficacy of cTACE stratified by main (main portal vein [MPV]) and branch (portal vein branch [PVB]) portal vein invasion. 76 A total of 1,333 patients received an estimated median of two (range: 2-4) TACE sessions. Response rates, defined by complete or partial response according to the mRECIST criteria, were similar: 14% (9-20%) and 16% (8-26%) (p ¼ 0.238).…”
Section: Advanced Stage (C)mentioning
confidence: 99%